Modulators of MHC class I-related protein 1-mediated antigen presentation - Kulicke, CA (2018)
The monomorphic MHC class I-related protein 1 (MR1) presents bacterial metabolites to mucosal-associated invariant T (MAIT) cells, an innate-like subset of T lymphocytes. The known MAIT-activating MR1 ligands are intermediates of riboflavin synthesis, a pathway specific to certain fungi and bacteria and, thus, intrinsically non-self for humans. Here, a combination of hypothesis-generating and hypothesis-testing approaches was used to identify novel modulators of this non-classical antigen presentation pathway. In particular, a functional genetic screening technique based on insertional mutagenesis of the near-haploid human cell line HAP1 was employed to discover novel players in MR1 antigen presentation and trafficking. The most significant positive regulator of MR1 surface expression identified in this screen was β2-microglobulin, confirming its indispensable role in the surface translocation of MR1. A number of other putative regulators of MR1 trafficking were taken forward into a CRISPR/Cas9-based validation approach and the ER-localised transporter ATP13A1 was found to affect MR1-mediated antigen presentation by modulating the size of the intracellular pool of MR1. In addition, the role of the soluble N-ethylmaleimide-sensitive factor activating protein receptor (SNARE) Sec22b in MR1-mediated antigen presentation was investigated as knock-down of Sec22b has previously been reported to control MHC class I-mediated cross-presentation. MR1 surface expression was reduced upon Sec22b knock-down and while the SNARE itself did not appear to play a role, RNA sequencing of a Sec22b deficient cell line revealed a number of potential regulators of MR1. Lastly, the capacity of cellular riboflavin transporters to mediate MR1 ligand import was investigated. Treatment with the riboflavin analogue lumiflavin resulted in decreased MR1 surface expression in various human cell lines by a mechanism that appeared to be independent of the inhibition of riboflavin import. Together, these data contribute to an increasing understanding of MR1-mediated antigen presentation, which is essential for harnessing the therapeutic potential of MAIT cells.